The Category of Definiteness/Indefiniteness in Sergei Dovlatov’s stories - GAZAROVA, DIANA (Bulletin of Yerevan University H: Russian Philology, 2021)
The paper touches upon the characteristics of the expression of the category of definiteness/indefiniteness in Sergei Dovlatov’s stories. Details of stories written before and after emigration period are compared from this perspective. According to the author the stories describing the life of emigrants are full of various functional grammatical expressive means typical for the category of definiteness/indefiniteness. And very often, in such cases, we can speak about relative, optional indefiniteness.
Keywords: category of definiteness-indefiniteness, indefinite pronouns, optional indefiniteness, emigration, one-member sentences